(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article presents the factors of managing the process of formation and development of teaching professional qualities of primary education students in a higher educational institution. acquisition and their practical application at a high level, professional competence does not mean the acquisition of separate knowledge and skills by a specialist, but the acquisition of integrative knowledge and actions in each independent direction, competence is the constant enrichment of specialized knowledge, to learn new information, to understand important social requirements, to be able to find new information, to process it and to apply it in one’s work, the professional competence that graduates of a higher education institution should acquire, the integration processes of acquiring it and the profession to be formed y recommendations are given about qualities.